Establishing the Validity and Reliability of Professional Learning Community (PLC) Inventory in Educational Sector - Thevi Jayaraman, Thiru Kali; Che Md Ghazali, Nor Hasnida Bt (International Journal of Academic Research in Progressive Education and Development, 2023)
The implementation of Profesional Learning Community (PLC) among secondary school teachers can enhance school capacity and excellence. To assess the execution of PLC, a reliable and valid instrument is necessary. This study aims to examine the validity, reliability and EFA of an instrument designed to evaluate the implementation of PLC. A well-designed instrument, which was distributed to 69 secondary school teachers in the form of a questionnaire for measuring the key components of PLC implementation and providing reliable data for research and assessment purposes. The Context, Input, Process and Product (CIPP) Evaluation Model, established by Daniel Stufflebeam, served as the foundation for the instrument. The content validity of the instrument was examined by experts, while the construct validity was assessed using internal consistency reliability or Cronbach Alpha. The pilot study findings suggest that the instrument is both reliable and valid, with 87 out of 91 items retained. This instrument provides a new perspective on measuring the implementation of Profesional Learning Community, especially in the school context.